“Do Good, Have Good”: A Serial Mediation Analysis of CSR with Customers’ Outcomes - Ahmed, Ishfaq; Nazir, Mian Sajid; Ali, Imran; Khalid, Arooj; Shaukat, Muhammad Zeeshan; Anwar, Farooq (Frontiers in Psychology, 2020)
CSR is envisaged to offer several outcomes, while customer-specific consequences are unclear or not obtained due attention, especially there is a dearth of literature that focuses on perceptual, attitudinal and behavioral outcomes in tandem. Against this backdrop, this study entails the investigation of perceptual (service quality), attitudinal (affective commitment) and behavioral (customer citizenship behavior) outcomes of CSR through a serial mediation mechanism. 994 responses, obtained from fast-food restaurants, highlights the fact that CSR influences customer citizenship behavior both directly and through serial mediation of service quality and affective commitment. The practical and theoretical usefulness of the study is also provided at the end.